Effects of distance to treatment on subsequent alcohol consumption. (4th March 2018) - Klinger, Jamie L.; Karriker-Jaffe, Katherine J.; Witbrodt, Jane; Kaskutas, Lee Ann
Abstract: Background : Distance and travel time are barriers to attending and completing drug and alcohol treatment. Few studies have examined proximity to treatment in relation to long-term outcomes. Objectives : Aims were to examine effects of distance to treatment on alcohol consumption in the year after treatment intake; assess moderation of distance effects by treatment type; and test mediators of effects of distance to treatment on later alcohol use. Methods : Data from clients in inpatient and outpatient alcohol treatment programmes in California ( n  = 560) were used in linear regression models. Results : There was a significant interaction between treatment type and distance on later drinking, with a significant positive association of distance to treatment with alcohol use after treatment for inpatient clients only. Among inpatient clients, none of the mediators significantly explained the relationship between a longer distance to treatment and greater subsequent alcohol use. Conclusion : Inpatient clients may benefit from customized post-treatment recommendations to identify recovery resources near home.